Lies, Damned Lies, or Statistics How to Tell the Truth with Statistics - Poritz, Jonathan A.; Open Textbook Library (Open Textbook Library, 2017)
This is a first draft of a free (as in speech, not as in beer, [Sta02]) (although it is free as in beer as well) textbook for a one-semester, undergraduate statistics course. It was used for Math 156 at Colorado State University-Pueblo in the spring semester of 2017.
Chapter 1. One-Variable Statistics: Basics -- Chapter 2. Bi-variate Statistics: Basics -- Chapter 3. Linear Regression -- Chapter 4. Probability Theory -- Chapter 5. Bringing Home the Data -- Chapter 6. Basic Inferences
In English.
Description based on online resource
Keywords: Mathematics -- Textbooks